Yale and Slavery A History - Blight, David W. (Yale University Press, 2024)
A comprehensive look at how slavery and resistance to it have shaped Yale University Award-winning historian David W. Blight, with the Yale and Slavery Research Project, answers the call to investigate Yale University's historical involvement with slavery, the slave trade, and abolition. This narrative history demonstrates the importance of slavery in the making of this renowned American institution of higher learning. Drawing on wide-ranging archival materials, Yale and Slavery extends from the century before the college's founding in 1701 to the dedication of its Civil War memorial in 1915, while engaging with the legacies and remembrance of this complex story. The book brings into focus the enslaved and free Black people who have been part of Yale's history from the beginning-but too often ignored in official accounts. These individuals and their descendants worked at Yale; petitioned and fought for freedom and dignity; built churches, schools, and antislavery organizations; and were among the first Black students to transform the university from the inside. Always alive to the surprises and ironies of the past, Yale and Slavery presents a richer and more complete history of Yale, the third-oldest college in the country, showing how pillars of American higher education, even in New England, emerged over time intertwined with the national and international history of racial slavery